IMPLEMENTASI SISTEM TANGGAP DARURAT KEBAKARAN PADA GEDUNG UTAMA DI INDUSTRI PUPUK - MUHAMMAD DIMAS; AGUS GETER EDY SUTJIPTO; ERRY YULIAN TRIBLAS ADESTA (Universitas Mahasaraswati K. Mataram, 2024)
A fire emergency response system is a series of procedures that must be carried out when a fire occurs to protect the safety of building occupants. The main objective of this final project is to ensure that the fire emergency response system in the main building of in the fertilizer industry. can function well when a fire occurs and can protect the safety of all main building employees. This research uses a qualitative research method which uses two types of data, namely primary data with in-depth interviews and observations, and secondary data from document reviews, company archives and literature studies. The results and discussion based on variables related to the implementation of the fire emergency response system can be concluded that the informants implemented the fire emergency response system procedures well and in accordance with established regulations. This is proven based on observations that in the main building of PT.X already has a fire emergency response system, such as a fire detection and alarm system, fire extinguishing system, evacuation routes, gathering points and other supporting equipment. Apart from that, there are also evacuation procedures, training and simulations, as well as maintenance of a fire emergency response system that is complete and in accordance with established regulations.